Synergistic Interplay of Covalent and Non‐Covalent Interactions in Reactive Polymer Nanoassembly Facilitates Intracellular Delivery of Antibodies. (19th November 2020) - Dutta, Kingshuk; Kanjilal, Pintu; Das, Ritam; Thayumanavan, Sankaran
Abstract: The primary impediments in developing large antibodies as drugs against intracellular targets involve their low transfection efficiency and suitable reversible encapsulation strategies for intracellular delivery with retention of biological activity. To address this, we outline an electrostatics‐enhanced covalent self‐assembly strategy to generate polymer‐protein/antibody nanoassemblies. Through structure–activity studies, we down‐select the best performing self‐immolative pentafluorophenyl containing activated carbonate polymer for bioconjugation. With the help of an electrostatics‐aided covalent self‐assembly approach, we demonstrate efficient encapsulation of medium to large proteins (HRP, 44 kDa and β‐gal, 465 kDa) and antibodies (ca. 150 kDa). The designed polymeric nanoassemblies are shown to successfully traffic functional antibodies (anti‐NPC and anti‐pAkt) to cytosol to elicit their bioactivity towards binding intracellular protein epitopes and inducing apoptosis. Abstract : A self‐immolative activated carbonate polymer was designed through structure–activity study for efficient protein/antibody encapsulation and redox‐sensitive release. Developed polymer–protein/antibody nanoassemblies demonstrated successful intracellular localization of cargoes with retention of cellular activities for catalysis or apoptosis.